Assessment of Work Life Balance (WLB) Among Employees in Banking Industry in Malaysia - Hartanto, Herlina (2012)
Since the introduction of Government Transformation Programme (GTP) and Economic Transformation Programme (ETP) towards achieving Vision 2020, development in all dimensions including the quality of work life of people becomes priority in Malaysia. While banking industry is known for long and inflexible working hour, this study explores work-life balance among employees in banking industry in Malaysia. This study therefore aims to assess the factors contributing to work-life balance in banking industry in Malaysia context. Nine semi-structured interviews were conducted to employers and employees in 3 local commercial banks. Data were analysed by using template analysis method. The findings mentioned workload, organizational support, managerial support and co-worker support as four factors contributing to work-life balance among employees. A brief recommendation to individual level, managerial level, organizational level and human resource department is covered.